From the Extolment of Freedom to the Reflection on Freedom: A Study of Carmen’s Absorption and Deviation from “The Gypsies” (Verse Version, 2024)
Mérimée’s novella Carmen is derived from Pushkin’s long narrative poem “The Gypsies”. “The Gypsies” is a Romantic work, where Pushkin affirms and sympathizes with the gypsy girl Zemfira’s life, which is integrated with nature, and her pursuit of freedom. Carmen, on the other hand, is a Realist work, where Mérimée adopts a cautious and critical attitude towards the concept of freedom exemplified by Carmen. Both Zemfira and Carmen are anarchists as defined by Proudhon; Pushkin extols the former, while Mérimée composes a lament for the latter.
Keywords: Pushkin; Zemfira; Mérimée; Carmen; Proudhon; Hobbes